Reliability and validity of an app-assisted tissue compliance meter in measuring tissue stiffness on a phantom model - Brandl, Andreas; Acikalin, Eda; Bartsch, Katja; Wilke, Jan; Schleip, Robert (PeerJ, 2024)
Background: Most methods for soft tissue stiffness assessment require high financial resources, significant technical effort, or extensive therapist training. The PACT Sense device was developed to be used in a wide range of applications and user groups. However, to date, there are no data on its validity and reliability. The aim of this study was to investigate the validity and reliability of the PACT device. Methods: A polyurethane phantom tissue model (PTM) mimicking the mechanical properties of the fascia profunda and the erector spinae muscle was used. Stiffness measurements with PACT were conducted by two independent investigators. For construct validity, correlations were calculated between the known stiffness of the PTM and values obtained with PACT. For concurrent validity, we determined the association between the PACT values and additional measurements with the established MyotonPRO device. To estimate interrater and intrarater (two measurements with an interval of 7 days) reliability, we used the intraclass correlation coefficient (ICC). Results: Correlation analysis (PTM/PACT) revealed very high concurrent validity (r = 0.99; p < 0.001), construct validity (PACT/MyotonPRO) was 0.87, p < 0.001. Both, interrater reliability (ICC = 0.85; p = 0.036) and intrarater reliability were good (ICC = 0.89; p < 0.001). Conclusions: The PACT provides valid and reliable stiffness measurements in tissue phantoms. Further studies in humans are needed to confirm its physiometric properties under in vivo conditions.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Elasticity; PACT sense; Soft tissue; Stiffness assessment; Tissue hardness